Clinical Outcomes and Quality of Life With an Ambulatory Counterpulsation Pump in Advanced Heart Failure Patients: Results of the Multicenter Feasibility Trial. (April 2020) - Uriel, Nir; Jeevanandam, Valluvan; Imamura, Teruhiko; Onsager, David; Song, Tae; Ota, Takeyoshi; Juricek, Colleen; Combs, Pamela; Lammy, Thomas; Patel-Raman, Sonna; Woolley, Joshua R.; Sayer, Gabriel; et al.
Abstract : Background: The NuPulseCV intravascular ventricular assist system (iVAS) provides extended duration ambulatory counterpulsation via a durable pump placed through the distal subclavian artery. Methods: We performed a prospective, single-arm, multicenter, US Food and Drug Administration-approved feasibility trial of iVAS therapy as a bridge to transplant or decision following the FIH (First-In-Human) trial. Results: Forty-seven patients were enrolled, and 45 patients (median 61 years old, 37 males, and 30 listed on United Network of Organ Sharing) received iVAS support for median 44 (25–87) days. There were no intraoperative complications. Success was defined as survival or transplant on iVAS therapy free from disabling stroke. Outcome success at 30 days (the primary end point of this study) and at 6 months was 89% and 80%, respectively. During 6 months of iVAS support, 2 patients died and 2 patients experienced disabling neurological dysfunction. Six-minute walk distance, 2-minute step test, and Kansas City Cardiomyopathy Questionnaire score improved during 4-week iVAS support. Conclusions: This feasibility trial demonstrated promising short-term outcomes of iVAS therapy with improved functional capacity and quality of life during the therapy. Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02645539. Abstract : Supplemental Digital Content is available in the text.